Forest burials in Denmark: Nature, non-religion and spirituality - Warburg, Margit (Approaching religion, 2023)
Burial in the forest is a recent, non-confessional alternative to the established cemeteries owned and run by the Evangelical Lutheran Church in Denmark. Danish forest burials fulfil common criteria for non-religion and they are an example of institutionalized non-religion. Their non-confessional character is emphasized in the information material directed towards potential buyers of forest burial plots. Forest burials appeal to both non-members and members of the Evangelical Lutheran Church; in fact, nearly two-thirds of those who had a forest burial by the end of 2021 were members of the church. I have participated in seven tours conducted at different forest burial sites, and I have interviewed nearly fifty participants about their motives for considering buying a forest burial plot. In my analyses, I structure the interviews along the three dimensions, knowing, doing, and being. I found that the motives for people to choose a forest burial reflected both non-religious and religious/spiritual considerations. Forest burials exemplify a religious complexity where nature, non-religion, religion, and spirituality intersect. In this complexity, I see the institution of forest burial as a non-religious vessel, which the buyers fill with their individual thoughts and acts.